MAKNA PERILAKU MINUM OBAT PADA PASIEN HIV/AIDS RAWAT JALAN DI VCT RSUP DR.KARIADI SEMARANG - Sari, Faradilla; Dewi, Endah Kumala; Kahija, Yohanis F. La (Jurnal Psikologi, 2014)
AbstractFor individuals with HIV/AIDS, making a decision to take a pill brings huge consequences. Taking medicine brings not only physical and psychological consequences, but also various social reactions, particularly those from family members and community. Individuals with HIV/AIDS also encountered social pressure and conflict with their environment. One might consider the pressure on the affected individuals as a challenge to continue their lives as well as resources to support them. The impact of taking medicines led individuals to give meaning to their behavior of pill taking. This qualitative study was conducted with phenomenological approach. Two women who were patients at Dr. Kariadi Hospital Semarang participated in this study. In collecting data, in-depth interview and observation were used. The meaning of taking medicines for patients with HIV was obtained from the subjective experience of participants in coping with pain. The results showed that participants gave meaning to taking medicines as a life saving due to her wish to see her children achieve their dreams.